Effects of posterior lumbar nonfusion surgery with isobar devices versus posterior lumbar interbody fusion surgery on clinical and radiological features in patients with lumbar degenerative diseases: a meta-analysis - Jianbin Guan; Tao Liu; Wenhao Li; He Zhao; Kaitan Yang; Chuanhong Li; Ningning Feng; Guozheng Jiang; Yongdong Yang; Xing Yu (Journal of Orthopaedic Surgery and Research, 2022)
Abstract Purpose The aim of this study was to systematically evaluate the efficacy of posterior lumbar isobar nonfusion with isobar devices versus posterior lumbar interbody fusion (PLIF) in the treatment of patients with lumbar degenerative diseases (LDDs). Materials and method We performed a literature review and meta-analysis in accordance with the Cochrane methodology. The analysis included a Group Reading Assessment and Diagnostic Evaluation assessments, Jadad Quality Score evaluations, and Risk of Bias in Randomized Studies of Interventions assessments. The PubMed, Ovid, EMBASE, Web of Science, MEDLINE, CNKI, VIP and WanFang databases were searched to collect and compare relevant randomized controlled trials and cohort studies of isobar nonfusion and PLIF in the treatment of lumbar degenerative diseases. The retrieval time was from database inception to June 2021. Two evaluators independently screened the literature, extracted data, and evaluated the quality of the included studies. Outcome measures of interest included low back pain, disability, and radiological features. The protocol for this systematic review was registered on INPLASY (2021110059) and is available in full on inplasy.com ( https://inplasy.com/inplasy-2021-11-0059/ ). Results Of the 7 RCTs, 394 patients met the inclusion criteria. The meta-analysis results showed that isobar nonfusion surgery shortened the surgical duration (P = 0.03), reducing intraoperative bleeding (P = 0.001), retained the ROM of surgical segment (P < 0.00001) and the ROM of the lumbar spine (P < 0.00001), and reduced the incidence of ASD (P = 0.0001). However, no significant difference in the postoperative ODI index (P = 0.81), VAS score of LBP (P = 0.59, VAS score of lower limb pain (P = 0.05, and JOA score (P = 0.27) was noted. Conclusions Posterior lumbar nonfusion surgery with isobar devices is superior to PLIF in shortening the surgical duration, reducing intraoperative bleeding, retaining the ROM of surgical segments and the lumbar spine to a certain extent, and preventing ASD. Given the possible publication bias, we recommend further large-scale studies.